Complications and Pathophysiology of COVID-19 in the Nervous System - Yu, Haiyang; Sun, Tong; Feng, Juan (Frontiers in Neurology, 2020)
Coronavirus disease (COVID-19) pandemic, caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has threatened the world’s public health. Most of patients with COVID-19 suffer from fever, cough, and fatigue. Critical patients can develop dyspnea and acute respiratory distress syndrome (ARDS). In addition to respiratory symptoms, neurological damage occurred in some patients. However, the mechanisms which SARS-CoV-2 invade nervous system has not been elucidated. In order to provide some reference for designing therapeutic strategies, we will discuss the COVID-19 related complications and potential mechanisms in nervous system in this review.